Analytical study and heat transfer analysis of on couple stress flow of hybrid nanofluid over a nonlinear stretching surface - Rehman, Ali; Khun, Ma Chau; Tlija, Mehdi; Jan, Rashid; İnç, Mustafa; Hussain, Shah (World Scientific Publ Co Pte Ltd, 2025)
This research paper investigates a two-dimensional couple stress flow of hybrid nanofluid (HN) over a nonlinear stretching surface with heat transfer analysis. HNs are well-known for their exceptional heat transfer properties compared to conventional fluids. The mathematical modeling of the problem involves the formulation of basic governing equations, namely, continuity, momentum and energy equations. To simplify the analysis, a similarity transformation technique is employed to convert the dimensional NLPDEs into dimensionless NODEs. Subsequently, the obtained governing equations are analytically solved using the HAM. The investigation explores the impact of several parameters, including magnetic field inclination, slip parameter, couple stress parameter, nanoparticle volume fraction, nonlinear stretching parameter, EN, thermophoresis parameter and PN. This study presents graphical representations of temperature and velocity distribution to visualize the effects of these parameters on the HN flow. Furthermore, different graphs and tables are employed to explain the impact of the factors on SF and NN. Notably, the results indicate that the HN exhibits significantly enhanced heat transfer properties over the base fluid, particularly under the influence of an inclined magnetic field. This research is expected to contribute to the advancement of the field of condensed nanostructure and nanomaterials, opening new avenues for further exploration in heat transfer enhancement applications.
Keywords: Hybrid nanofluid; magnetic field; viscous dissipation; nonlinear stretching sheet; homotopy analysis method; nonlinear coupled equations